European industrial relations: An increasingly fractured landscape? - Paul Marginson (University of Warwick, Industrial Relations Research Unit, 2017)
In the face of continuing European market and economic integration, European industrial relations has become more fractured. This fracturing is occurring in two senses. First, the main institutional pillars of the industrial relations dimension of the European social model (or models) are weakening. Second, common features of industrial relations across countries are no longer so apparent. Further, industrial relations outcomes such as wages and conditions have become more unequal and less solidaristic. The immediate causes of this fracturing are eastern enlargement of the EU, and the nature of the responses to the financial and economic crisis propounded by the European authorities and some national governments. These have sought to accelerate European integration by removing perceived institutional rigidities. At an underlying level, a more fractured industrial relations landscape is the result of asymmetries as between countries in the effects and impact of market and economic integration and the further exacerbation of the imbalance between negative and positive integration measures in favour of the former. The paper concludes with proposals, directed at the EU as well as national level, which could stem or even reverse the decline in the institutional pillars of European industrial relations and result in a less fractured landscape.
Keywords: 330; Arbeitsbeziehungen; EU-Staaten